Construction and thermal properties of nano-structured polymer bonded explosives with graphene. Issue 119 (18th November 2015) - Lin, Congmei; He, Guansong; Liu, Jiahui; Pan, Liping; Liu, Shijun
Abstract : The addition of graphene is a simple and novel route for improving the thermal conductivity of polymer bonded explosives. Abstract : 1, 3, 5-Triamino-2, 4, 6-trinitrobenzene (TATB)-based polymer bonded explosives (PBXs) modified with graphene were prepared by the water suspension methods. The effects of coating methods and graphene content on the thermal conduction properties were investigated. Reference raw TATB-based PBX samples were also tested and compared with the results obtained from the nanocomposites filled with graphene. The experimental results indicated that the dispersion and concentration of graphene in the nanomaterials could play an important role in the thermal behaviors. Compared with the nanocomposites with outer-coating graphene, the corresponding PBXs with inner-coating graphene presented a higher thermal conductivity due to better dispersion of graphene in the composites with the aid of ultrasound vibration. The nonlinear dependence of the thermal conductivity of TATB-based PBXs on the graphene content was observed. When the content of inner-coating graphene came to 2 wt%, the thermal conductivity of TATB-based PBX increased by 105.5%, with values of 1.122 W m −1 K −1 . The Agari model was adopted to analyze the thermal behaviors of TATB-based PBXs filled with graphene. With the incorporation of graphene, the thermal conduction mechanism of TATB-based PBXs changed from a series model to partial parallel model. Additionally, the testing temperatures had a dual effect on the thermal conductivity of TATB-based PBXs. With increasing temperature, the thermal conductivity initially exhibited a sharp drop, and then a little fluctuation was observed in the temperature range of 50–70 °C. Finally, the thermal conductivity of PBXs reduced with temperature again.